FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN NYERI HAID (DYSMENORRHEA) PADA REMAJA PUTRI DI WILAYAH KERJA PUSKESMAS MEKAR SARI KABUPATEN BANYUASIN - Eko Dwi Lestari; Eka Afrika; Eka Rahmawati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Dysmenorrhea is pain during menstruation. Dysmenorrhea consists of a complex of symptoms in the form of lower abdominal cramps that radiate to the back. (Marmi, 2015). Based on data from the World Health Organization (WHO) in 2015 there were 1,769,425 people (90%) of women who experienced dysmenorrhea with 10-15% experiencing severe dysmenorrhea. The purpose of this study was to determine the relationship between anxiety, physical activity and nutritional status simultaneously with the incidence of dysmenorrhea in adolescent girls in the working area of ​​the Mekarsari Health Center, Banyuasin Regency. This study used an analytical survey method with a cross sectional design, the variables studied were the independent variables (the relationship between anxiety, physical activity, and nutritional status) and the dependent variable (dysmenorrhea) were measured and collected together. This research was conducted in the working area of ​​the Mekarsari Health Center, Banyuasin Regency with a sample of 60 people. This analysis was conducted to determine the relationship between the independent variables (anxiety, physical activity, and nutritional status) and the dependent variable (dysmenorrhea). value 0.860, physical activity variable p value 0.003 and nutritional status variable p value 0.000, which means that there is a significant relationship between nutritional status and the incidence of dysmenorrhea. There is no relationship between anxiety, physical activity and nutritional status simultaneously with dysmenorrhea in the working area of ​​the Mekarsari Health Center, Banyuasin Regency  Keywords             : Anxiety, Physical Activity, Nutritional Status and Dysmenorrhea